MARKETING STRATEGY OF AI-SUPPORTED ISLAMIC FINANCIAL INSTITUTIONS IN THE ERA OF SOCIETY 5.0 - Sona, Muklas Ary; Yuli Dianto, Alfin; Moh. Saiful Musthofa (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
The marketing strategy of Islamic financial institutions in the era of Society 5.0 is crucial for gaining a competitive advantage based on technology. The application of Artificial Intelligence (AI) can optimize customer service, product personalization, and operational efficiency in Islamic banking. By leveraging AI, Islamic financial institutions can provide more relevant experiences to customers through big data analysis and process automation. Furthermore, the use of AI in credit decision-making and risk management supports the principles of Islamic finance by ensuring transparency and avoiding practices contrary to Islamic law. However, challenges related to technological infrastructure and alignment with Sharia principles must be addressed to achieve long-term success. This study aims to analyze how AI implementation in marketing strategies can strengthen the position of Islamic financial institutions in the Society 5.0 era.